IBCL-124: Interim Analysis of ZUMA-5: A Phase 2 Study of Axicabtagene Ciloleucel (Axi-Cel) in Patients with Relapsed/Refractory Indolent Non-Hodgkin Lymphoma (R/R iNHL) - Jacobson, Caron A.; Chavez, Julio C.; Sehgal, Alison R.; William, Basem M.; Munoz, Javier; Salles, Gilles; Casulo, Carla; Munshi, Pashna N.; Maloney, David G.; Vos, Sven de; Reshef, Ran; Leslie, Lori A.; et al. (Clinical lymphoma, myeloma and leukemia, 2020)
Here, we report interim results from ZUMA-5, a Phase 2 study of axi-cel, an autologous anti-CD19 chimeric antigen receptor (CAR) T cell therapy, in patients with relapsed/refractory iNHL. Adults with relapsed/refractory follicular lymphoma (FL) or marginal zone lymphoma (MZL) after ≥2 lines of therapy (including an anti-CD20 monoclonal antibody with an alkylating agent) were eligible. Patients were leukapheresed and received conditioning chemotherapy followed by axi-cel at 2 × 106 CAR T cells/kg. The primary endpoint was objective response rate (ORR) by central review (Cheson, et al. J Clin Oncol. 2014). Secondary endpoints included duration of response (DOR), progression-free survival (PFS), overall survival (OS), safety, and blood levels of CAR T cells. As of 8/20/19, 94 patients (80 FL; 14 MZL) received axi-cel (median follow-up, 11.5 months). Median age was 63 years, 51% of patients had ≥3 FLIPI, 59% had high tumor bulk, 66% progressed < 2 years after first chemoimmunotherapy (POD24), and 73% were refractory to the last treatment. Of 87 patients evaluable for efficacy, ORR was 94% (79% complete response [CR] rate). Patients with FL (n=80) had an ORR of 95% (80% CR rate). Patients with MZL (n=7) had an ORR of 86% (71% CR rate). Overall, 68% of patients had ongoing responses as of the data cutoff. Updated data will be presented. Of 94 patients evaluable for safety, 83% experienced Grade ≥ 3 adverse events, most commonly neutropenia (33%) and anemia (28%). Grade ≥ 3 cytokine release syndrome (CRS) and neurologic events (NEs) occurred in 11% and 19% of patients, respectively. Median times to onset of CRS and NEs were 4 and 7 days; median durations were 6 and 14.5 days. There were 2 Grade 5 adverse events: multisystem organ failure in the context of CRS (related to axi-cel) and aortic dissection (unrelated to axi-cel). Median peak and AUC0-28 CAR T cell levels were 44 cells/μL and 490 cells/μL × day, respectively. Axi-cel showed significant clinical benefit, with high response rates, and a manageable safety profile in patients with relapsed/refractory iNHL. Funding provided by Kite, a Gilead Company.